Comparison of outcomes for transjugular intrahepatic portosystemic shunt creation: Viatorr versus Fluency versus a bare stent/Fluency stent combination - Weizhi Li; Mengying Liu; Sheng Guan; Pengxu Ding; Jia Yuan; Yan Zhao; Peijie Li; Fuquan Ma; Hui Xue (CVIR Endovascular, 2024)
Abstract Purpose To compare clinical outcomes of transjugular intrahepatic portosystemic shunt (TIPS) created with the single covered-uncovered stent (Viatorr TIPS Endoprosthesis) versus covered stent (Fluency) versus a combination of covered and uncovered stent. Materials and methods From May 2016 and July 2019, a total of 180 liver cirrhosis patients with recurrent variceal bleeding underwent TIPS creation with single covered-uncovered stent (n = 63) or covered stent (n = 41) or a covered and uncovered stent combination (n = 76). Shunt dysfunction, rebleeding, overt hepatic encephalopathy and mortality was estimated using the Kaplan–Meier method and compared with the log-rank test. Results The difference of baseline characteristics among these three groups were not significant. The included patients had a median age of 51 years (IQR 43–61), and 101 (56.1%) were men. The 1-year and 2-year shunt dysfunction rates were 1.6% and 3.2% in the single covered-uncovered stent group, 7.3% and 7.3% in the covered stent group and 5.3% and 6.6% in the combination group, respectively. There was no significant difference among groups [Hazard Ratio (HR) (95%CI): 1 vs 2.29 (0.38 − 13.72) vs 2.10 (0.41 − 10.83); P = 0.913]. No significant differences in the incidence of all-cause rebleeding were observed between the groups at 1 year (Viatorr vs Fluency vs combination: 11.1% vs 17.1% vs 10.5%) as well as 2 years (15.9% vs 17.1% vs 11.8%), with the HR (95%CI) being 1 vs 1.27 (0.5—3.21) vs 0.74 (0.30–1.82); P = 0.475). The 1-year and 2-year incidence of overt hepatic encephalopathy were 30.2% and 30.2% in the single covered-uncovered stent group, 22.0% and 22.0% in the covered stent group and 25.0% and 25.0% in the combination group, respectively. However, there was no significant difference among these three groups (P = 0.402). In addition, there was no significant difference in the 1-year and 2-year mortality (6.3% and 7.9% vs. 4.9% and 9.8% vs. 6.6% and 9.2%, P = 0.606). Conclusion No significant difference was observed among different stent groups. Fluency covered stent and the generic bare stent/Fluency covered stent was not an unreasonable alternative to the Viatorr stent for TIPS creation.